(untitled) (Journal of Information Technologies in Education (ITE), 2011)
In this article the information about assignment of the pedagogical program method “Library of electronic obviousness “Algebra for 7-9th forms” and its main characteristics are given. Also methodic aspects of carrying the algebra lessons are shown.